2019
DOI: 10.3390/cells8091087
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Apoptotic Effect of ASC-Exosomes in an In Vitro ALS Model and Their Proteomic Analysis

Abstract: Stem cell therapy represents a promising approach in the treatment of several neurodegenerative disorders, including amyotrophic lateral sclerosis (ALS). The beneficial effect of stem cells is exerted by paracrine mediators, as exosomes, suggesting a possible potential use of these extracellular vesicles as non-cell based therapy. We demonstrated that exosomes isolated from adipose stem cells (ASC) display a neuroprotective role in an in vitro model of ALS. Moreover, the internalization of ASC-exosomes by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 50 publications
(66 reference statements)
0
52
0
Order By: Relevance
“…It has been suggested for example in pancreatic cancer that TEV could promote M2 macrophage polarisation by conveying HIF-1α protein or that TEV could convey entire or cleaved Bcl-xL protein, as well as other proteins and molecules (miRNA or lncRNA) that promote the anti-apoptotic pathways after internalisation by cells, and could even lead to the production of Bcl-xL or other anti-apoptotic proteins in TEV recipient cells [ 44 , 65 , 66 ]. Thus, we further investigated whether we could detect molecular changes in the slightly less responsive hypoxic naïve C26 and RAW 264.7 cells to DOX after the pretreatment with normoxic TEV and DOX-elicited TEV ( Figure 4 C and Figure 5 C).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested for example in pancreatic cancer that TEV could promote M2 macrophage polarisation by conveying HIF-1α protein or that TEV could convey entire or cleaved Bcl-xL protein, as well as other proteins and molecules (miRNA or lncRNA) that promote the anti-apoptotic pathways after internalisation by cells, and could even lead to the production of Bcl-xL or other anti-apoptotic proteins in TEV recipient cells [ 44 , 65 , 66 ]. Thus, we further investigated whether we could detect molecular changes in the slightly less responsive hypoxic naïve C26 and RAW 264.7 cells to DOX after the pretreatment with normoxic TEV and DOX-elicited TEV ( Figure 4 C and Figure 5 C).…”
Section: Discussionmentioning
confidence: 99%
“…Bonafede et al reported the anti-apoptotic effect of ASC-exosomes in an ALS cell model, supported by increasing of anti-apoptotic protein and decreasing of pro-apoptotic proteins through proteomic analysis of exosomes. 96 Furthermore, neuroprotective effect of ASC-exosomes was confirmed in superoxide dismutase 1 (G93A) murine model. 97 …”
Section: Applications Of Evs In Cns Diseasementioning
confidence: 94%
“…Treatment of neurons from G93A ALS mice with human adipose-derived MSC-Exos alleviated aggregation of superoxide dismutase 1, and normalized the cellular phenotype, restoring to normal the levels of mitochondrial proteins including p-CREB and PGC-1α[ 145 ]. Subsequently, two studies by the same group showed that mouse adipose tissue-derived MSC-Exos exerted an anti-apoptotic effect and rescued the function of mitochondria in an in vitro model of ALS[ 146 , 147 ]. MS is a chronic demyelinating disease caused by CNS inflammation and immune dysfunction, which can result in severe physical disability.…”
Section: Therapeutic Potential Of Msc-exos In Regenerative Medicinementioning
confidence: 99%